2021
DOI: 10.1111/ijcp.14923
|View full text |Cite
|
Sign up to set email alerts
|

A novel enema method can prevent infectious complications of transrectal ultrasound‐guided prostate biopsy: A single‐centre experience

Abstract: Background TRUS biopsy is the preferred method for diagnosing prostate cancer, but it can cause infectious complications that arise with the contribution of fluoroquinolone resistance. We aimed to explore the potential protective effect of a second rectal enema before biopsy. Methods From January 2015 to December 2020, 419 patients were assessed retrospectively. Patients with a history of anticoagulant use, uncontrolled diabetes, urological surgery, prostate biopsy or recent hospitalisation or overseas travel,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Sepsis, defined with a SOFA score greater than 2 [11], and positive urine culture were observed in 0.7% of all men. However, no statistically significant difference in the rate of sepsis after transrectal ultrasound-guided prostate biopsy was detected between the two cohorts (0.7 versus 0.5%, P ¼ 0.54) [16]. Of note, in two studies [15,16], men at high risk for infection (e.g.…”
Section: Definitions Of Sepsis Vary Across Studies Which Makes Compar...mentioning
confidence: 94%
See 2 more Smart Citations
“…Sepsis, defined with a SOFA score greater than 2 [11], and positive urine culture were observed in 0.7% of all men. However, no statistically significant difference in the rate of sepsis after transrectal ultrasound-guided prostate biopsy was detected between the two cohorts (0.7 versus 0.5%, P ¼ 0.54) [16]. Of note, in two studies [15,16], men at high risk for infection (e.g.…”
Section: Definitions Of Sepsis Vary Across Studies Which Makes Compar...mentioning
confidence: 94%
“…However, no statistically significant difference in the rate of sepsis after transrectal ultrasound-guided prostate biopsy was detected between the two cohorts (0.7 versus 0.5%, P ¼ 0.54) [16]. Of note, in two studies [15,16], men at high risk for infection (e.g. those with immunodeficiency or other selected comorbidities) were excluded from the final analysis.…”
Section: Definitions Of Sepsis Vary Across Studies Which Makes Compar...mentioning
confidence: 97%
See 1 more Smart Citation
“…People with combined diabetes have poor body resistance, and some studies have shown that diabetes can promote the growth of Escherichia coli and induce pyelonephritis [25]. Moreover, diabetic patients often develop insulin resistance, which may also promote the release of various inflammatory factors, resulting in hypoxia, fibrosis, centrocyte infiltration, and other changes in the prostate tissue, and with the prolongation of diabetes, the body's immune-regulatory function may decrease even under glycemic control, which may increase the chance of infection after TRUSPB [26].…”
Section: Cases Of Infectionmentioning
confidence: 99%